2018
DOI: 10.31237/osf.io/nxzep
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reinforcement Learning vs Genetic Algorithms in Game-Theoretic Cyber-Security

Abstract: Penetration testing is the practice of performing a simulated attack on a computer system in order to reveal its vulnerabilities. The most common approach is to gain information and then plan and execute the attack manually, by a security expert. This manual method cannot meet the speed and frequency required for efficient, large-scale secu- rity solutions development. To address this, we formalize penetration testing as a security game between an attacker who tries to compro- mise a network and a defending ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Niculae built a more realistic multi-agent system, where included the interactions among attackers, defenders and normal users [56]. In the system, ten attack actions, three defense actions and three normal user actions were designed.…”
Section: Pentest Based On Pomdpmentioning
confidence: 99%
“…Niculae built a more realistic multi-agent system, where included the interactions among attackers, defenders and normal users [56]. In the system, ten attack actions, three defense actions and three normal user actions were designed.…”
Section: Pentest Based On Pomdpmentioning
confidence: 99%
“…Manual penetration tests, although effective, can hardly meet all security requirements that are constantly changing and evolving (Niculae, 2018). Furthermore, they require specialized knowledge which, in addition to presenting a high cost, is typically slower.…”
Section: Related Workmentioning
confidence: 99%
“…The alternative is automated tools that, although faster, often do not adapt to the context and uniqueness of each application. In (Niculae, 2018), the author developed a reinforcement learning strategy capable of compromising a system faster than a brute force and random approach. This concluded that it is possible to build an agent capable of learning and evolving over time so that it can penetrate a network.…”
Section: Related Workmentioning
confidence: 99%
“…Pen testing simulations [17,20] have been used to train red agents using reinforcement learning. These simulations use a realistic action space to enable agents to learn how to attack a network.…”
Section: Related Workmentioning
confidence: 99%